(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
Factors such as population growth, the increase of industries, the widening of economic frontiers and the intensification of agriculture generate, every day, more waste of unknown effects, waste without destination, irreversible pollution, rampant deforestation, causing a global concern for health the planet. Spaces of outstanding biological diversity, such as the Amazon, are the most affected in this context. Sustainable development urgently needs to stop being seen as a goal and to be seen as something emerging. The speed attained by the degradation of the environment is alarming and the insufficiency of the current instruments used to contain it is notorious. Keywords: Environmental Court; Environment; Amazon; International Court; Environmental Law.